Evidence for internal tether-cutting in a flare/coronal mass ejection observed by Messenger, Rhessi, and Stereo - MC ATEER, ROBERT THOMAS JAMES; GALLAGHER, PETER THOMAS (My University, 2010)
The relationship between eruptive flares and coronal mass ejections (CMEs) is a topic of ongoing debate, especially regarding the possibility of a common initiation mechanism. We studied the kinematic and hydrodynamic properties of a well-observed event that occurred on 2007 December 31 using data from MESSENGER, RHESSI, and STEREO in order to gain new physical insight into the evolution of the flare and CME. The initiation mechanism was determined by comparing observations to the internal tether-cutting, breakout, and ideal magnetohydrodynamic (MHD) models. Evidence of pre-eruption reconnection immediately eliminated the ideal MHD model. The timing and location of the soft and hard X-ray sources led to the conclusion that the event was initiated by the internal tether-cutting mechanism. In addition, a thermal source was observed to move in a downward direction during the impulsive phase of the event, followed by upward motion during the decay phase, providing evidence for X- to Y-type magnetic reconnection.
PUBLISHED
Keywords: Astrophysics; Sun: coronal mass ejections (CMEs)